The Labor Market Indicators Alteration in Syria during the period 2000-2020 (Analytical Study) - محلا, رباب (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Labor market indicators represent the most important quantitative and qualitative tools that help in determining labor market trends and understanding the nature of its performance. In Syria, during the period 2001-2011, the labor market was greatly affected by local and regional circumstances, and suffered from the repercussions of the war on all economic and social levels, after 2011. So, it have been necessary, to treatise in labor market indicators and expertise their important denotations, which help in planning and setting the necessary economic and operational policies to improve labor market conditions and advance the reality of the labor force in the obtainable conditions. In this context, the research presents a study and analysis of the most important labor market indicators in Syria during the period 2000-2020, as unemployment indicators, contribution to economic activity, and the composition of workers, in particular. We based on data from the Central Bureau of Statistics and labor market surveys during the studied period .